2002
DOI: 10.1177/0011000002302010
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention in Counseling Psychology

Abstract: This study examined primary prevention articles published in four counseling journals from 1985 to 1999. The authors’ results indicated a relative paucity of prevention-focused literature in counseling journals. Specifically, 52 (1.29%) of the 4,028 articles published over this 15-year period focused on primary prevention. The 52 articles were reviewed for type of article, article topic, setting, and general populations sampled. The lack of prevention articles in counseling journals is problematic as journals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Professional journals represent an avenue for continuing education and an opportunity to fill gaps in training; however, recent reviews of major counseling journals found little attention given to prevention (Matthews, 2004;O'Byrne, Brammer, Davidson, & Poston, 2002), yet these same journals publish articles that describe prevention as integral to the field (e.g., Hage, 2003;Romano & Hage, 2000b) There are several steps that psychologists can take to develop competency in prevention (Conyne, 2004;Gullotta & Bloom, 2003a), including, but not limited to, (a) developing community partnerships in which faculty and students collaborate with community personnel to design, deliver, and evaluate prevention projects; (b) complementing the focus on remediation by continuing efforts to develop prevention-specific opportunities within the profession, such as Web sites and special interest groups; (c) incorporating components that address prevention concepts, practices, and experiences within existing courses; (d) disseminating prevention-focused research and practice activities; (e) seeking external funding for prevention projects by collaborating with personnel from related disciplines in which funding may be more available (e.g., public health, criminal justice); (f) connecting prevention with remediation rather than treating each as discretely separate approaches; (g) advocating for prevention-sensitive research, training, and practice within APA and other relevant professional associations (e.g., American Counseling Association, American School Counseling Association, National Association of School Psychologists, and National Association of Social Workers); and (h) educating the American population directly through popular media and community presentations about the everyday value of prevention in their lives.…”
Section: Psychologists Are Encouraged To Develop Knowledge Of Prevmentioning
confidence: 99%
“…Professional journals represent an avenue for continuing education and an opportunity to fill gaps in training; however, recent reviews of major counseling journals found little attention given to prevention (Matthews, 2004;O'Byrne, Brammer, Davidson, & Poston, 2002), yet these same journals publish articles that describe prevention as integral to the field (e.g., Hage, 2003;Romano & Hage, 2000b) There are several steps that psychologists can take to develop competency in prevention (Conyne, 2004;Gullotta & Bloom, 2003a), including, but not limited to, (a) developing community partnerships in which faculty and students collaborate with community personnel to design, deliver, and evaluate prevention projects; (b) complementing the focus on remediation by continuing efforts to develop prevention-specific opportunities within the profession, such as Web sites and special interest groups; (c) incorporating components that address prevention concepts, practices, and experiences within existing courses; (d) disseminating prevention-focused research and practice activities; (e) seeking external funding for prevention projects by collaborating with personnel from related disciplines in which funding may be more available (e.g., public health, criminal justice); (f) connecting prevention with remediation rather than treating each as discretely separate approaches; (g) advocating for prevention-sensitive research, training, and practice within APA and other relevant professional associations (e.g., American Counseling Association, American School Counseling Association, National Association of School Psychologists, and National Association of Social Workers); and (h) educating the American population directly through popular media and community presentations about the everyday value of prevention in their lives.…”
Section: Psychologists Are Encouraged To Develop Knowledge Of Prevmentioning
confidence: 99%
“…This reality is not surprising since counseling psychology graduate programs prepare students to be knowledgeable about traditional theories of counseling and psychotherapy and career development but give little if any attention to theories or models that more directly apply to a prevention perspective (Blustein, Goodyear, Perry, & Cypers, 2005;Hage et al, 2007;O'Byrne, Brammer, Davidson, & Poston, 2002). The typical curriculum is heavily oriented to remedial models of care and focuses primarily on individuals in crisis (Albee, 2000;Chwalisz, 2003;Gerstein, 2006;Sprinthall, 1990).…”
mentioning
confidence: 99%
“…Counseling psychology has become increasingly self-reflective about its own scholarly discourse in recent years (e.g., Flores, Rooney, Heppner, Browne, & Wei, 1999;O'Byrne, Brammer, Davidson, & Poston, 2002;Perez, Constantine, & Gerard, 2000;Pope-Davis, Ligiero, Liang, & Codrington, 2001). It is crucial for us to occasionally reflect on our history.…”
mentioning
confidence: 99%